Quasi-continuous time-stretched photon Doppler velocimetry - Lv, Linjie; Yang, Yongjun; Wu, Tengfei; Han, Jibo; Ma, Pengmou; Chen, Xiangmiao; Khan, Abdul Qayyum (Frontiers in Physics, 2022)
In transient high-speed scenes such as chemical explosions, magnetic compression, electric explosion, and laser-driven flyer, the target object can accelerate from 0 to tens of km/s in a few nanoseconds. The time-stretched photon Doppler velocimetry uses the time-stretched interferometry to downscale the frequency of the Doppler shift signal in the optical domain, which breaks through the bandwidth limitations of photoelectric detectors and electrical digital to analog converters. A quasi-continuous time-stretched photon Doppler velocimetry (QT-PDV) is proposed in this paper, for the measurement of microsecond high-speed movement events. On the principle of hardware optical path, the velocity signal of the target object is encoded on multiple stretched chirp pulses, avoiding sampling interruptions and trigger condition limitations; in the signal demodulation methods, the error compensation algorithm is used to compensate for the frequency shift signal, which reduces the system error caused by the displacement and increases the effective recording time. This paper adopts the high-power nanosecond laser to drive the metal film to produce a high-speed target, where beat frequency was downscaled to 2.2 GHz from 4.4 GHz.